Aktualny zakres i zasady ochrony gruntów rolnych w Polsce - Oryński, Andrzej (Present Extent and Rules of Agricultural Land Protection in Poland, 2005)
Agricultural land protection in Poland concentrates both on the amount and the quality. The conditions of excluding land from agricultural production, legal procedures as well as costs and taxes cause the demand for agricultural land to decrease. The tendency is to be seen especially as far as the best and most effective agricultural land is concerned. Those who cause the negative influence on agricultural land are obliged to cover the losses and other costs which the agriculture has to bear. They additionally have to make the damaged land useful again and therefore industry is forced to use solutions which would minimize their negative impact on the environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 155-162